Designing dynamic circuit response - Feucht, Dennis (Raleigh, NC SciTech Publishing, 2010)
By deriving the complex-frequency expression for beta from the BJT hybrid-pi model, we can write the beta-dependent impedance transformations at base and emitter nodes in a general form. When these impedances are represented graphically on a reactance chart, the effects of circuit element variations on circuit behavior, especially HF resonances, become evident. The frequency dependent beta transform is also applicable to FETs and single-pole feedback amplifiers. They show the same impedance gyrations as the BJT, so the BJT results can be easily extended to them also.
Transient and frequency response -- Dynamic response compensation -- High-frequency impedance transformations.
Electronic reproduction.
Keywords: Frequency response (Dynamics); Transients (Dynamics); Electronic circuit design; Bipolar transistors; Electronic apparatus and appliances; Logic design; Semiconductors; Electronic books